PROFIL SOSIAL EKONOMI DAN STATUS GIZI PETANI DI LOMBOK TENGAH NUSA TENGGARA BARAT - Dadang Sukandar (Jurnal Gizi dan Pangan, 2007)
Socio-conomic and nutritional status are nutrition problems in Indonesia. Solution to overcome this problem is therefore needed. Objectives of this study are 1) to asses  socio-economic, 2) to asess nutritional status of community and 3) to improve nutritional status  through conducting training on food,nutrition, sanitation and hygiene. Study was conducted in Central Lombok, Nusa Tenggara Barat, from December 1995 to November 2006. A sample of size 63 households was drawn randomly from household population of size 316. The households population is household farmer who are beneficiary of Special Program for Food Secutity, Food and Acgriculture Organization. Data were analyzed quantitatively and qualitatively and presented in table. Reseacrh results show that level of income of farmer is still very low. Average income of farmer is only Rp 99.141 per capita per month.  Most portion of expenditure or as much as 72% is spent for food. There are still many husbands-wives who have nutrition problem. As much as 30% of husbands are thin and 4% are overweight. As much as 11% wives are thin and 11% are overweight. After attending trainning, the knowledge on nutrition and food of the farmers increase significantly, therefore it is hoped  that their knowledge can improve their nutritional status.